Analysis of Split Ticket Voting in the 2024 General Election in Sibolga City - Lubis, Abdullah Fattah Al Mauludi; Situmorang, Tonny P (UNIVERSITAS PAKUAN, 2025)
This study examines the phenomenon of split ticket voting in the 2024 General Election in Sibolga City, where voters cast their ballots for a presidential candidate and a legislative party from different political parties. The objective is to understand the factors influencing this behavior and its relation to local political perceptions. The research employs a descriptive qualitative approach, using interviews, observations, and documentation as data collection techniques. The data indicate that voters separated their choices based on evaluations of candidate figures and the effectiveness of political performance at both the local and national levels. The findings show that voting behavior is no longer grounded in party loyalty but rather in rational evaluations of differing needs across electoral levels. In conclusion, split ticket voting in Sibolga City represents an expression of political rationality by the community in responding to the complexities of electoral democracy.